프로젝트 관리자로서의 발주자 사업수행평가 프레임워크 개발 - 김종훈; 이현수; 박문서; 박상혁; 이인범; Kim, Jonghoon; Lee, Hyun-Soo; Park, Moonseo; Park, Sanghyuk; Lee, Inbeom (한국건설관리학회 논문집, 17(5), 2016)
Owner's participation on a construction project can alter the success of a construction project. In general, success of a construction project is measured by project schedule and cost decrease without considering the role an owner has in a project. As a result, this research developed a framework for the project evaluation form and after extracting a total of 9 project critical success factors (CSF) and 27 sub-CSF. AHP method was utilized to evaluate the importance factor of each CSFs. Setting a goal for each CSFs at the beginning of a project and comparing the values at the completion of the project utilizing the project evaluation form will allow a systematic evaluation and management of a project. Solution Map was introduced and Solution Tool was suggested in order to utlize the evaluation results effectively. In the future studies, various project cases needs to be supplemented for further verification and a solution based on the evaluation result needs to be developed that can be applied to construction projects. 건설프로젝트의 성공은 프로젝트 관리자로서의 발주자의 참여가 중요하다. 그 이유는 일반적으로 프로젝트의 성공을 공기단축, 비용절감 등으로 측정하지만, 기존 성공을 측정하는 방법으로는 발주자의 역할을 고려하지 않고 있기 때문이다. 따라서 본 연구는 프로젝트 관리자로서 발주자를 위한 사업수행평가서를 개발하기 위해 통해 총 9개의 프로젝트 CSF와 27개의 sub-CSF를 도출하였다. 도출된 CSFs의 중요도를 평가하기 위해 AHP 기법을 활용하였으며, 기존 존재하던 PDRI 방법을 활용한 사업수행평가서를 개발하였다. 사업수행평가서를 활용하면 각 CSFs에 대한 초기 목표값을 설정하고 프로젝트 완료 후 평가 결과의 비교를 통해 프로젝트를 효과적으로 관리하고 평가할 수 있다. 평가결과를 실무적으로 활용하기 위한 솔루션 맵을 제시하고 활용 가능한 솔루션 툴을 제안한다. 추후 연구에는 실질적인 검증을 위해 다양한 프로젝트 사례를 추가할 뿐만 아니라 평가를 통해 현장에 적용 가능한 솔루션 툴을 지속적으로 개발해야한다.